Visualization of microscale cavitating flow regimes via particle shadow sizing imaging and vision based estimation of the cone angle - Ghorbani, Morteza; Alcan, Gokhan; Unel, Mustafa; Gozuacik, Devrim; Ekici, Sinan; Uvet, Huseyin; Sabanovic, Asif; Kosar, Ali (ELSEVIER SCIENCE INC, 2016)
Recent studies show the destructive effect of the energy released from the collapse of cavitation bubbles, which are generated in micro domains, on the targeted surfaces. The cavitation phenomenon occurs at low local pressures within flow restrictive elements and strongly affects fluid flow regimes inside microchannels which results in spray formation. Extended cavitation bubbles toward the outlet of the microchannel, droplet evolution, and spray breakup are among crucial mechanisms to be considered in spray structure. In this study, various spray structures under the effect of hydrodynamic cavitation were recorded using a high speed visualization system. Acquired images were analyzed and characterized using several image processing algorithms. In this regard, the fluid flow with ascending upstream pressures from 10 to 120 bar were passed through a microchannel with an inner diameter of 0.152 mm. The spray at the outlet of the microchannel was analyzed for these pressures in four different segments. Particle Shadow Sizing (PSS) imaging and several image processing techniques such as contrast stretching, thresholding and morphological operations were employed to identify the flow regimes in the separated segments. In addition, a vision based estimation technique that utilizes a Kalman filter was developed to estimate cone angle of the spray. Furthermore, classification of fluid flow regimes and morphological characteristics of the spray structure were outlined based on the cavitation number. (C) 2016 Published by Elsevier Inc.
Keywords: Cavitation; Cone angle; Kalman filter; Microchannel; Spray; Visualization; LARGE-EDDY SIMULATION; VORTEX FLOW; NOZZLE; ATOMIZATION; ORIFICE; Thermodynamics; Engineering; Physics